Regioselective Transformations of Unsaturated Systems Catalyzed by Low-Valent Nickel: Cycloaddition, Hydrosilylation, and Dicarbofunctionalization - Kim, Gun Ha; Jeon, Ji Hwan; Jung, Byunghyuck; Rohde, Jan-Uwe; Hong, Sung You (Synlett, 2025)
In this Account, we describe our recent research progress in the development of the functionalization of unsaturated substrates catalyzed by low-valent nickel. In particular, we discuss nickel-catalyzed azide–alkyne cycloaddition (NiAAC), [2 + 2 + 2] cycloaddition of diynes and nitriles, hydrosilylation of alkynes, and dicarbofunctionalization of 1,3-enynes. Moreover, we highlight our mechanistic studies aimed at elucidating catalytically active nickel intermediates, thereby contributing to the understanding and expansion of nickel-catalyzed synthetic methodologies.1 Introduction2 Nickel(0)-Catalyzed Cycloaddition Reactions3 Nickel(I)-Catalyzed Hydrosilylation and Dicarbofunctionalization Reactions4 Conclusion and Outlook
Keywords: unsaturated systems; nickel; cycloaddition; hydrosilylation; dicarbofunctionalization; regioselectivity; reaction mechanisms